Synthesis, characterization and electrochemical performance of activated carbon supported MnO2 for electrochemical capacitor - Luong Thi Thu Thuy; Le Van Khu; Nguyen Thi Kim Lien (Vietnam Journal of Science and Technology, 2018)
MnO2 was synthesized by adding activated carbon into KMnO4 solution and stirred in a magnetic or ultrasonic stirrer. The obtained MnAC samples were characterized by means of XRD, TGA, TPR-H2, SEM and BET. All samples are amorphous and have porous structure. MnAC-M prepared by magnetic stirring have higher manganese content, earlier reduction temperature, smoother surface area while MnAC-U prepared by ultrasonic stirring have larger specific surface area and pore volume.